TOXIC-BIOLOGICAL ASSESSMENT OF SLAUGHTER ANIMAL MEAT AT TREATING WITH DETERGENT-DISINFECTION AGENTS IN PRODUCTION AND TURNOVER - Bogatko, N.M. (Scientific Progress & Innovations, 2019)
Studies have established the toxic-biological evaluation of beef, pork, lamb, and goat meat when treating it with detergent-disinfection agents at production facilities, storing at wholesale depots, and for selling in su-permarkets and agro-markets through the test-object culture of Tetrachymena pyriformis infusoria. Experi-mental samples of meat of slaughtered animals frozen for production and storage at wholesale depots at tem-peratures of −2 to −3 °C for 21−22 days; for the sale of chilled meat in supermarkets at a temperature of 4±2 °C for 3−4 days; for sales in the agro-food markets of meat chilled at temperatures from 0 to 6 °C for 3−4 days, corresponded to doubtful freshness in terms of organoleptic, physical-chemical and microscopic pa-rameters. Express methods were established for meat production facilities: of 12 beef samples − 4 samples were treated with a formalin solution with a mass fraction of 10 %; 15 samples of pork− 6 samples were treat-ed with a solution of hydrogen peroxide with a mass fraction of 5 %; at wholesale depots: of 13 beef samples− 5 samples were treated with chlorine solution (chlorine activity of 3 %); of 14 samples of pork − 8 samples were treated with alkaline detergents, and of 8 samples of lamb − 3 samples were treated with a solution of potassium permanganate with a mass concentration of 5 %. Toxic meat was found by treating beef with a solu-tion of formalin (10 %) − 11.31 %, which was characterized by a decrease in the infusoria number by 8.84 times (p<0.1) and chlorine solution (chlorine activity of 3 %) − 16.01 %, which in the indicators was charac-terized by a probable decrease in the infusoria number by 6.25 times (p<0,001) as compared with the control indicators. The toxicity percentage after treating pork with a solution of hydrogen peroxide (5 %) − 41.22% was slightly higher, which in the indicators was characterized by a probable decrease in the infusoria number of by 2.43 times (p<0.001); and alkaline detergents - 32.91 %, which in the indicators was characterized by a probable decrease in the infusoria number by 3.04 times (p<0.001); and lamb with a solution of potassium permanganate (5 %) − 37.77 %, which in the indicators was characterized by a probable decrease in the infu-soria number by 2.65 times (p<0.001) in comparison with the control indicators. The smallest biological value of meat was noted in beef treated with formalin solution (10 %) at the meat production capacity of 42.92 %, where the infusoria number significantly decreased by 2.33 times (p<0.001) as compared with the control indi-cators. The highest biological value among meat treated with detergents was observed in pork for storage at capacity and was treated with a solution of hydrogen peroxide (5 %)− in 60.00 %, where the infusoria number was significantly reduced by 1.67 times (p<0.001) as compared with the control indices. Beef sold in the su-permarket at 4±2 °C for 3−4 days and treated with sodium bicarbonate solution was slightly toxic (67.88 %) as compared with the control (100 % non-toxic), which was characterized by a significant decrease in infusoria number – by 1.47 times (p<0.01). The study also found that toxic were: pork treated with a solution of hydro-gen peroxide (5 %) − 42.45 %, which was characterized by a probable decrease in the infusoria number by 2.36 times (p<0.001); goat meat treated with a solution of potassium permanganate (5 %) − 24.56 %, which in the indicators was characterized by a probable decrease in the infusoria number by 4.07 times (p<0.001) as compared with the control indicators. The most toxic meat was found at treating lamb meat with alkaline disin-fectants − 13.62 %, which was characterized by7.34 times decrease (p<0.1) in the infusoria number as com-pared with the control parameter. Chilled meat, which was sold on the agro-food market at temperatures from 0 to 6 °C for 3−4 days, was also toxic and accordingly amounted to percentages: beef treated with chlorine solution (chlorine activity 3 %) − 17.11 %, which in the indicators was characterized by a probable decrease in the infusoria number by 5.84 times (p<0.001); pork treated with alkaline detergents − 19,84 %, which in the indicators was characterized by a probable decrease in the infusoria number by 5.04 times (p<0.001); lamb meat treated with a solution of potassium permanganate (5 %) − 32,69 %, which in the indicators was charac-terized by a probable decrease in the infusoria number by 3.06 times (p<0.01), and goat meat treated with a solution of acetic acid (10 %) – 45,15 %, which in the indicators was characterized by a probable decrease in the infusoria number of by 2.21 times (p<0.01) as compared with the control indicators. Under microscopy, droplets of culture for 24 hours of toxic meat of slaughtered animals at treating with detergent-disinfection agents were observed cell death, reduced reproduction, the presence of cysts, deformed cells; in low-toxic beef –the inhibition of infusoria growth, decrease in activity and mobility (unnatural movements), small number ofdeformed cells.